The mental health effects of social media on young adult South Africans in the COVID-19 pandemic: a thematic analysis of social media posts by Rhodes University students - Jubase, Hlumelo (Rhodes University, Faculty of Humanities, Department of Sociology)
The COVID-19 pandemic in South Africa has been mainly discussed in terms of its socioeconomic effects and loss of life. While these are important, its mental health effects are given attention in this dissertation. In particular, this is explored through social media platforms, which saw increased usage as a result of regulations on movement to slow the Virus' spread. This is explored during the hard lockdown (or 'Alert Level 5') and further, focuses on young adults, key users of social media platforms. Max Weber's 'social action theory' and Michel de Certeau's 'theory of everyday life' are drawn on, which help to analyse social relations from an individual level; and are used to explore the kinds of expressions made on a social media platform, and what can be said in mental health terms. These theoretical frameworks are applied to a university "Confessions" page, used mostly by young adults, where submissions were made anonymously. Findings indicate a great deal of trauma associated with the COVID-19 pandemic, but also evidence of the emergence of collective responsibility. They show the immense sacrifices made by participants for the opportunity of an education, and provide a window into the kinds of subjectivities experienced by South African young adults. Further, they show the importance of having more substantive mental health discussions in South Africa, a country familiar with traumatic experiences.
Keywords: COVID-19 Pandemic, 2020-; Social media and college students -- South Africa -- Makhanda; College students Mental health -- South Africa -- Makhanda; Social media Influence; Action theory